Rheumatology symptoms and syndromes - Benenson, E. V. (Efim V.); SpringerLink (Online service). (London New York Springer, 2011)
Rheumatology: Symptoms and Syndromes organizes the rheumatic diseases in the form of syndromes as stable combinations of symptoms, and links these to morphological manifestations. This presentation of the rheumatic diseases provides a pedagogical framework for differential diagnosis in rheumatology. To further aid the teacher and student, Professor Efim Benenson provides algorithms of clinical reasoning based on morphology and pathophysiology. Professor Benensonâ??s practice-oriented, didactic approach, and innovative organization of the rheumatic diseases is a valuable diagnostic aid to practicing rheumatologists and those teaching or training in rheumatology. Readers are recommended the companion book, Rheumatology: Clinical Scenarios, for further reading on Professor Benensons's organization of the rheumatic diseases.
Articular disorders -- Diseases of the spine -- Soft-tissue rheumatism and related disorders -- Regional arthrological and musculoskeletal syndromes -- Paraneoplastic syndromes (PNS) in rheumatology -- Algorithms in articular and musculoskeletal disorders: integrated diagnostic screening program: staged diagnostics -- Algorithms in arthrological and musculoskeletal disorders -- General symptoms (BVAS = maximum of 3 out of 63 points) -- Involvement of connective tissue structures -- System-/organ involvement -- (Auto) immunological phenomena and serological diagnostics -- Treatment-induced and associated conditions and diseases -- Integrated diagnostic screening program staged diagnostics -- Algorithms for connective tissue disease and vasculitis.
Electronic reproduction.
Keywords: Rheumatology -- Diagnosis; Rheumatology -- Treatment; Electronic books